Management of adrenocortical carcinoma in Slovenia - Bokal, Urška (Radiology and oncology (Ljubljana), 2025)
Background. Adrenocortical carcinoma (ACC) is a rare cancer that presents significant diagnostic and therapeutic challenges. We analyzed the management and estimated survival of ACC patients in Slovenia over a 17-year period. Patients and methods. Patients registered in the National Cancer Registry and treated from 2000 to 2017 were included. The survival and prognostic factors were assessed using the Kaplan-Meier method and Cox regression, respectively. Results. Forty-eight patients were included in our analysis. At the time of diagnosis, 6%, 42%, 25% and 27% had stage according European Network for the Study of Adrenal Tumors (ENSAT) I, II, III and IV, respectively. Adjuvant treatment with mitotane was assigned to 18 of 34 potentially eligible patients. High-risk patients treated with adjuvant mitotane showed a reduced probability of death, although the difference was not statistically significant. Relapses had numeri cally higher rate of R1 resection and higher Ki67. Eleven patients underwent first-line therapy with etoposide, doxo rubicin, cisplatin and mitotane (EDP-M). Their median progression-free survival was 4.4 months. The median overall survival of entire cohort was 28.9 and the median disease-specific survival (DSS) was 36.2 months. The 5-year DSS rate of ENSAT I, II, III and IV were 100%, 56%, 50% and 0%, respectively. The prognostic value of ENSAT stage and Helsinki score regarding overall survival was confirmed with the multivariate analysis. Conclusions. The 5-year DSS of our ENSAT II patients was worse than reported in contemporary cohorts. Suboptimal surgery and inconsistent adjuvant therapy with mitotane might have contributed to this outcome. Better outcomes of this rare disease might be accomplished with dedicated teams including various specialties, working towards optimal staging, diagnostic and therapeutic measures.
Keywords: adrenocortical carcinoma; adrenokortikalni karcinom; ENSAT stage; sistemsko zdravljenje; stopnja ENSAT; systemic treatment